Estimates of genetic and environmental (co)variances for vertebral deformities and vaccine-induced side effects in Atlantic salmon - Gjerde, Bjarne; Karlsson-Drangsholt, Tale Marie; Ødegård, Jørgen; Finne-Fridell, Frode; Thorland, Ingunn; Hjelde, Kirsti (Frontiers in Animal Science, 2025)
Vaccination is an effective tool to prevent disease outbreaks in Atlantic salmon. However, oil-adjuvant vaccines, which may lead to negative side effects such as adhesions of abdominal organs and melanin deposits on abdominal organs and the abdominal wall, have been linked to vertebral deformities. The main objective of this study was to estimate both the genetic and environmental (residual) correlations between vaccine-induced side effects and vertebral deformities and the genetic correlation between vertebral deformities measured at different ages. The recorded fish were the offspring of 85 sires and 150 dams from SalmoBreed (year-class 2007) and included two groups of vaccinated fish: pre-smolts exposed to 17°C freshwater for 3 months (FW) and a group of post-smolts (SW) evaluated after 6 (SW6) and 12 (SW12) months in a net cage in the sea. Adhesions of abdominal organs and viscera (score 0–6) and melanin deposits on abdominal organs and the abdominal wall (score 0–3) were evaluated by trained personnel, and vertebral deformities were recorded using radiography. The frequency of vertebral deformities was 6.4%, 5.2%, and 6.4% for the FW, SW6, and SW12 groups, respectively. Fused vertebrae were the most common type of deformity in all groups, with fused vertebrae (4.2%) in the FW group and a low percentage of missing intervertebral space in the SW6 (0.5%) and SW12 (0.6%) groups. The mean adhesion scores for the FW, SW6, and SW12 groups were 2.06, 1.68, and 1.46, respectively, while the mean melanin scores were 0.95, 1.49, and 1.45. The heritability on the liability scale for fused vertebrae was of medium magnitude for the FW (0.28 ± 0.11) group as well as for the SW6 (0.20 ± 0.10) and the SW12 (0.20 ± 0.10) groups. Across the experimental groups, the genetic and residual correlations of fused vertebrae with adhesion and melanin scores were all close to and not significantly different from zero. Therefore, no evidence was found of a genetic or environmental association between the negative side effects of vaccination (adhesions and melanin deposits) and fused vertebrae in Atlantic salmon.